Pengaruh Store Atmosphere, Kualitas Produk, dan Kualitas Layanan terhadap Kepuasan Konsumen di Seniman Coffee Studio - KUSUMAWATHI, NI WAYAN GIANA; DARMAWAN, DWI PUTRA; SURYAWARDANI, I G.A OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Effect of Store Atmosphere, Product Quality, and Service Quality on Consumer Satisfaction at the Seniman Coffee Studio The rapid development of coffee shops in the Ubud sub-district is certainly the main competitors of the Seniman Coffee Studio to attract consumers. This research was conducted to determine the characteristics of consumers of Seniman Coffee Studio and the effect of store atmosphere, product quality, and service quality on consumer satisfaction at Seniman Coffee Studio. This study uses descriptive analysis and analysis of Structural Equation Modeling (SEM) through the Partial Least Squares (PLS) approach. The method of obtaining data in this study was through distributing questionnaires at Seniman Coffee Studio. The results of this study indicate that store atmosphere has a direct effect of 23.8% on customer satisfaction, product quality has a direct effect of 41% on customer satisfaction, and for service quality it also has a direct effect of 41.7% on consumer satisfaction at the Seniman Coffee Studio. Store atmosphere, both exterior and interior, at Seniman Coffee Studio needs to be improved, seeing its effect is smaller than the quality of the product and the quality service on customer satisfaction.